2009
DOI: 10.1016/j.drugalcdep.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating motivational enhancement therapy adherence and competence among Spanish-speaking therapists

Abstract: Despite the fact that the number of Hispanic individuals in need of treatment for substance use problems is increasing internationally, no studies have investigated the extent to which therapists can provide empirically supported treatments to Spanish-speaking clients with adequate fidelity. Twenty-three bilingual Hispanic therapists from five community outpatient treatment programs in the United States were randomly assigned to deliver either three sessions of motivational enhancement therapy (MET) or an equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 35 publications
(47 reference statements)
3
45
0
Order By: Relevance
“…Relative to therapeutic strategies used during the sessions, counselors talked informally with their clients less often than they used MET consistent strategies or techniques to assess substance use or related psychosocial factors. In contrast, on average informal discussion occurred more frequently than any of the MET inconsistent strategies (e.g., direct confrontation) or strategies involving treatment approaches from other theoretical orientations (e.g., coping skills training) (see Santa Ana et al, 2009 for details about ITRS item frequencies in the Spanish MET trial).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Relative to therapeutic strategies used during the sessions, counselors talked informally with their clients less often than they used MET consistent strategies or techniques to assess substance use or related psychosocial factors. In contrast, on average informal discussion occurred more frequently than any of the MET inconsistent strategies (e.g., direct confrontation) or strategies involving treatment approaches from other theoretical orientations (e.g., coping skills training) (see Santa Ana et al, 2009 for details about ITRS item frequencies in the Spanish MET trial).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, informal discussion was measured by the frequency of its use (adherence), not the competence in which it was rendered. Psychometric analyses of the ITRS used in the Spanish MET trial (Santa Ana et al, 2009) and the English MET trial (Martino et al, 2008) confirmed good to excellent levels of interrater reliability (ICCs ranging from .60 to .96 in the Spanish MET trial and from .66 to .99 in the English MET trial) and a two-factor model among the MET consistent items: a) fundamental skills that underpin the empathic and collaborative stance of MET such as open-ended questions, reflective statements, and motivational interviewing style or spirit; and b) advanced skills for evoking client motivation for behavior change, such as heightening discrepancies and change planning (Martino et al, 2008; Santa Ana et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations